Formation of Euphemism in the Bidayuh Language : A Study on the Bukar–Sadong and Biatah Dialects - Angelia Marjorie, Fabian; Yvonne Michelle, Campbell (University of Hawai'i Press, 2024)
Euphemism is a language phenomenon that reflects the culture of a particular language community. The studies on euphemism strategies are necessary as they enhance the body of knowledge on how language is shaped by and shapes culture while fostering better communication. This paper examined and compared the euphemism strategies used by two Bidayuh dialects, Bukar–Sadong and Biatah, while utilizing Warren’s Model in identifying the strategies. Warren’s Model consists of four devices: semantic innovation, word formation, phonemic modification, and loan words with seventeen euphemism strategies. The data for this study were collected through an in-depth, open-ended interview with four Bukar–Sadong and four Biatah informants of fifty to sixty-nine years old, chosen according to the NORMF criteria. The findings revealed that both dialects comprised three devices: semantic innovation, word-formation device, and loan words, with the Biatah dialect additionally comprising the phonemic modification device. Both dialects showed extensive usage of the semantic innovation device, with wide usage of the implication strategy in Bukar–Sadong and the metaphor strategy in Biatah. Meanwhile, only in Biatah, euphemisms were derived from the phonemic replacement or remodeling strategy of the phonemic modification device.